An Enquiry into Self-Monitoring: its relationships to physical illness and psychological distress - Heian, James; Chen, Alex (School of Management Working Papers, 1990)
A major general purpose of this paper is therefore to identify the principal aggregate and structural impacts which result from a substantial switch to petroleum products excise revenue from crude oil levy revenue. Industrial ·sector interfuel substitution effects are explicitly allowed for, under conditions of no net change in nominal or real liquid fuel tax receipts. Specific account is also taken of two important strands of the Australian government’s pre-1988 oil regulatory framework, namely the import parity pricing (IPP) and domestic allocation systems for crude oil.